Latest Advances in Green Extraction of Polyphenols from Plants, Foods and Food By-Products - Andrea Palos-Hernández; Ana M. González-Paramás; Celestino Santos-Buelga (Molecules)
Phenolic compounds present in plants and foods are receiving increasing attention for their bioactive and sensory properties, accompanied by consumers’ interest in products with health benefits derived from natural rather than artificial sources. This, together with the sustainable development goals for the 21st century, has driven the development of green extraction techniques that allow obtaining these compounds with the safety and quality required to be applied in the food, cosmetic and pharmaceutical industries. Green extraction of natural products involves practices aiming at reducing the environmental impact of the preparation processes, based on using natural or less-polluting solvents, lower energetic requirements and shorter extraction times, while providing greater efficiency in the recovery of target compounds. In this article, the principles of sustainable extraction techniques and the advances produced in recent years regarding green isolation of polyphenols from plants, food and food waste are reviewed.